Structural requirements of oleosin domains for subcellular targeting to the oil body. - van Rooijen, G J (1995)
We have investigated the protein domains responsible for the correct subcellular targeting of plant seed oleosins. We have attempted to study this targeting in vivo using "tagged" oleosins in transgenic plants. Different constructs were prepared lacking gene sequences encoding one of three structural domains of natural oleosins. Each was fused in frame to the Escherichia coli uid A gene encoding beta-glucuronidase (GUS). These constructs were introduced into Brassica napus using Agrobacterium-mediated transformation. GUS activity was measured in washed oil bodies and in the soluble protein fraction of the transgenic seeds. It was found that complete Arabidopsis oleosin-GUS fusions undergo correct subcellular targeting in transgenic Brassica seeds. Removal of the C-terminal domain of the Arabidopsis oleosin comprising the last 48 amino acids had no effect on overall subcellular targeting. In contrast, loss of the first 47 amino acids (N terminus) or amino acids 48 to 113 (which make up a lipophilic core) resulted in impaired targeting of the fusion protein to the oil bodies and greatly reduced accumulation of the fusion protein. Northern blotting revealed that this reduction is not due to differences in mRNA accumulation. Results from these measurements indicated that both the N-terminal and central oleosin domain are important for targeting to the oil body and show that there is a direct correlation between the inability to target to the oil body and protein stability.